HUBUNGAN SCHOOL CONNECTEDNESS DAN DUKUNGAN TEMAN SEBAYA DENGAN SCHOOL WELLBEING PADA SISWA SMP MUHAMMADIYAH 5 TULANGAN - Nastiti, Dwi; Fadilah, Amiratul (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
School Wellbeing is important for students, especially for students who have low School Wellbeing quality. The phenomenon found is that there are still students whose School Wellbeing is less than optimal, especially in the aspects of having and loving. This study aims to examine the Relationship between School Connectedness and Peer Support with School Wellbeing in Students of SMP Muhammadiyah 5 Tulangan. The research approach used is quantitative with a correlational method. The study population was 359 students with a sample of 177 students. The researcher used the Probability Sampling technique with the stratified random sampling method. Data collection used the School Connectedness scale with a reliability of 0.890, the Peer Support scale with a reliability of 0.896, and the School Wellbeing scale with a reliability of 0.776. The data analysis technique used product concept analysis and was calculated using the JASP program. The results of this study state that there is a significant positive relationship between School Connectedness and School Wellbeing (r=0.548), with a p-value .001 (.005), and a significant positive relationship between Peer Support and School Wellbeing (r=418), with a p-value .001 (.005).